2004
DOI: 10.1002/acp.1065
|View full text |Cite
|
Sign up to set email alerts
|

The effects of protective helmet use on physiology and cognition in young cricketers

Abstract: Many studies have reported physiological and cognitive decrements following heat stress. Of particular concern in cricket are the possible negative effects of sustained protective helmet use, as this leads to an increase in heat-related stress. Correct and rapid decision making, and focused attention are essential for efficient performance whilst batting, and it is possible that helmet usage could impair such processes. In a repeated-measures, randomized crossover study, physiological, self-report, and cogniti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 26 publications
1
17
1
Order By: Relevance
“…The small number of participants is a limitation of this study, but one that is difficult to overcome when the sample is international athletes. Our sample was similar to those in many studies of young or elite athletes (Neave et al, 2004;Périard et al, 2014), particularly in fencing (Devienne, Ripoll, Audiffren, & Stein, 2000;Williams & Walmsley, 2000). Moreover, every year, only 15 young fencers competing at the national or international level are accepted into the French Caribbean Fencing Pole.…”
Section: Limitationsmentioning
confidence: 54%
“…The small number of participants is a limitation of this study, but one that is difficult to overcome when the sample is international athletes. Our sample was similar to those in many studies of young or elite athletes (Neave et al, 2004;Périard et al, 2014), particularly in fencing (Devienne, Ripoll, Audiffren, & Stein, 2000;Williams & Walmsley, 2000). Moreover, every year, only 15 young fencers competing at the national or international level are accepted into the French Caribbean Fencing Pole.…”
Section: Limitationsmentioning
confidence: 54%
“…The former study used a simple arithmetic addition task, whereas the latter used a simple reaction time task. In contrast, the two other studies mentioned in the Introduction reported at least one measured cognitive parameter being affected by wearing a helmet (Hancock and Dirkin, 1982;Neave et al, 2004). Hancock and Dirkin (1982) used a central and peripheral visual choice reaction time, whereas Neave et al (2004) used an extensive proprietary cognitive test battery.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast, the two other studies mentioned in the Introduction reported at least one measured cognitive parameter being affected by wearing a helmet (Hancock and Dirkin, 1982;Neave et al, 2004). Hancock and Dirkin (1982) used a central and peripheral visual choice reaction time, whereas Neave et al (2004) used an extensive proprietary cognitive test battery. This pattern of findings across the four earlier studies could suggests that any effect of wearing a helmet is sufficiently subtle that it can only be seen when people's cognitive resources are highly taxed.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, it appears that neither exogenous heat penetration nor metabolic heat dissipation are covered within the relevant standards for protective headwear, including Wre helmets. Thus, with few exceptions (Armstrong et al 2002;Brühwiler 2007;Holland et al 2002;Neave et al 2004), the thermodynamics and physiological impact of many forms of protective helmets have not been thoroughly evaluated.…”
Section: Introductionmentioning
confidence: 97%